2016
DOI: 10.1073/pnas.1516321113
|View full text |Cite|
|
Sign up to set email alerts
|

PDK1–Akt pathway regulates radial neuronal migration and microtubules in the developing mouse neocortex

Abstract: Neurons migrate a long radial distance by a process known as locomotion in the developing mammalian neocortex. During locomotion, immature neurons undergo saltatory movement along radial glia fibers. The molecular mechanisms that regulate the speed of locomotion are largely unknown. We now show that the serine/threonine kinase Akt and its activator phosphoinositide-dependent protein kinase 1 (PDK1) regulate the speed of locomotion of mouse neocortical neurons through the cortical plate. Inactivation of the PDK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 61 publications
4
36
0
Order By: Relevance
“…Inhibition or activation of the PDK1-Akt pathway changed the locomotion speed by 20 to 30%, 24 but did not abrogate migration altogether. It is assumed that changing the speed of neuronal migration in entire neuronal population will not affect layer structure.…”
Section: Regulation Of Locomotion Speed By the Pdk1-akt Pathwaymentioning
confidence: 90%
See 4 more Smart Citations
“…Inhibition or activation of the PDK1-Akt pathway changed the locomotion speed by 20 to 30%, 24 but did not abrogate migration altogether. It is assumed that changing the speed of neuronal migration in entire neuronal population will not affect layer structure.…”
Section: Regulation Of Locomotion Speed By the Pdk1-akt Pathwaymentioning
confidence: 90%
“…12,17,31 To circumvent these limitations, we conditionally knocked out PDK1 either in the central nervous system or in postmitotic cortical neurons. 24 Both mutant brains showed disorganized layer structure in the neocortex, implying migration defects. BrdU birthdating analysis and live-imaging of neuronal migration in organotypic brain slice culture revealed that PDK1 deletion slows down locomotion within the CP in both mutant brains, demonstrating that PDK1 is required for an appropriate speed of bipolar locomotion.…”
Section: Regulation Of Locomotion Speed By the Pdk1-akt Pathwaymentioning
confidence: 99%
See 3 more Smart Citations